Adult Safeguarding Observed How Social Workers Assess and Manage Risk and Uncertainty - Dixon, Jeremy (Policy Press, 2023)
Chapters 1, 3 and 5 are available Open Access under CC-BY licence. Safeguarding adults at risk of abuse or neglect is a core area of social work practice but knowledge of how social workers make adult safeguarding decisions is limited. Applying recent sociological and ethnographic research to this area for the first time, this book considers how adult safeguarding practice is developing, with a focus on risk management. The author explores how social workers conduct safeguarding adults assessments, work with multiple agencies and involve service users in risk decisions. The book is essential reading for those wishing to understand how risk and uncertainty are managed within frontline adult social work and how current practice can be improved.